Wedding of the waters : the Erie Canal and the making of a great nation - Bernstein, Peter L. (New York : W.W. Norton, 2005)
"The account of how the Erie Canal forever changed the course of American history"--Provided by publisher.
Smooth sailing -- Hudson's wrong turn -- Washington's pivot -- Canal maniacs -- "A canal to the moon" -- The sublime spectacle -- The extravagant proposal -- The expedition -- War and peace -- The shower of gold -- Digging the ditch -- Boom, bust, bonds -- Rude invective -- Unwearied zeal -- A noble work -- The pageant of power -- The wedding of the waters -- No charge for births -- The prodigious artery -- The granary of the world.
Includes bibliographical references (p. 413-423) and index.
Keywords: Erie Canal (N.Y.); United States -- Economic conditions